Stopping cross sections of TiO2 for H and He ions - Limandri, Silvina Paola; Fadanelli, Raul C.; Behar, Moni; Nagamine, Luis C. C. M.; Fernandez Varea, Jose M.; Abril, Isabel; Garcia Molina, Rafael; Montanari, Claudia Carmen; Aguiar, Julio C.; Mitnik, Dario Marcelo; Miraglia, Jorge Esteban; Arista, Nestor Ricardo (Springer, 2014)
Fil: Limandri, Silvina Paola. Comision Nacional de Energia Atomica. Fundación Jose A. Balseiro; Argentina